KONFLIK SOSIAL DALAM NOVEL YAKOU KANRANSHA KARYA MINATO KANAE - Ismi Nursipa, Siti; Anwar, Fithyani; El Risman, Yunita (Universitas Hasanuddin, 2023)
This study aims to explain the social conflicts and factors that cause social conflicts in the novel Yakou Kanransha by Minato Kanae. This research is analyzed using a structural approach. Meanwhile the research method used in this research is descriptive qualitative method. The data sources used in this study is a Japanese novel with the title Yakou Kanransha which was published in Japan in 2010. Overall, this novel talks about the various conflicts experienced by the characters in each of their families. The characters involved in the conflict in this novel. From the results of the study, it can be concluded that there are several social conflicts that occur in this novel, including: rudeness, fighting, killing, bullying and social class discrimination. In addition, this data analysis found that the factors that cause social conflicts include differences of opinion, differences of interest, differences of views, and differences of stance and belief.